Ekstraksi ion krom dalam asam nitrat dengan teknologi membran cair untuk limbah industri penyamakan kulit - Nurhajati, Dwi Wahini; Prayitno, Prayitno; Kismolo, Endro (Majalah Kulit, Karet, dan Plastik, 1999)
The objective of the research was to use of liquid membrane emulsion technique for the extraction of chrom in the nitrate acid solution. The liquid membrane phase as emulsion consists of kerosene as the solvent, sorbitan monooleat (span-80) as the surfactant, trioktil amin, as the carrier, natrium hidroksida as the internal phase. The optimum conditions obtained for making membrane, the liquid membrane phase was consists of organic phase (O), the internal liquid phase (W) with the ratio of O/W = 1, the concentration sorbitan monooleat (span-80) in the membrane phase was 4%(v/v), the optimum time to achieve a emulsion was 5 minutes, the rate of stirring for membrane 8000 rpm. The  optimum conditions obtained for extraction chrom ion as of chrom nitrate  from solution with percentage of liquid membrane extraction used of 97,8% and the percentage of liquid membrane extraction used of 97,8% and the percentage of liquid-liquid extraction of 81,24% were as follow : the concentration of nitric acid in external phase was 3M, the concentration of tri oktil amin in the membrane phase was 5% (v/v), the concentration of natrium hidroksida in internal phase was 1% (v/v), the extraction time was 15 minutes and volume ratio of membrane phase and external phase was 1 : 3. The addition of Fe and Zn ions solution decreased the percent extraction of chrom ion. INTISARI Penelitian ini bertujuan untuk meneliti teknik membran cair dalam ekstraksi krom pada larutan asam nitrat. Fasa membran yang berupa emulsi terdiri dari kerosene sebagai pelarut, sorbitan monooleat (span-80) sebagai surfaktan, tri oktil amin (TOA), sebagai zat pembawa serta natrium hidroksida sebagai fasa internal. Kondisi optimum yang diperoleh untuk pembuatan membrane cair, fasa membran terdiri dari fasa organic (O), fasa internal (W) dengan perbandingan O/W = 1, konsentrasi sorbitan monooleat dalam fasa membran 4%(v/v), waktu optimum pembuatan emulsi 4 menit, kecepatan pengadukan 8000 rpm. Kondisi optimum yang diperoleh untuk mengekstraksi krom dari larutan yang mengandung krom nitrat dengan prosen ekstraksi membran-cair sebesar 97,80% dan proses ekstraksi cair-cair sebesar 81,24% adalah sebagai berikut : konsentrasi asam nitrat dalam fasa eksternal adalah 3M, konsentrasi tri oktil amin dalam fasa membran adalah 5%(v/v), konsentrasi natrium hidroksida, dalam fasa internal 1%(v/v), 1 M dan lamanya waktu ekstraksi ialah 15 menit dan perbandingan  volume fasa membran dan volume fasa eksternal adalah 1 : 3. Penambahan ion ferro dan seng dalam larutan krom akan menurunkan prosen ekstraksi krom